'Ground Zero' of Brexit: London as an international financial centre - Hall, S; Wojcik, D (Elsevier, 2018)
This critical reviews section explores the implications of Brexit from a financial geography perspective in a number of different geographical settings. These range from the epicentre of Brexit in London's financial district, to its implications for the wider UK economy before extending the analysis to financial centres in Europe and Asia.